1987
DOI: 10.1149/1.2100532
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Deposited Silicon Nitride for Gallium Arsenide Encapsulation

Abstract: The composition and annealing characteristics of plasma deposited silicon nitride encapsulating films on ion implanted gallium arsenide have been investigated. X-ray photoelectron spectroscopy was employed to study the surface of the semi-insulating GaAs substrates after cleaning in organic solvents, and HCt, HF, and NH4OH solutions prior to encapsulation. The composition of silicon nitride films deposited with 30 kHz RF excitation was determined through Auger electron spectroscopy and infrared spectroscopy as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Nuclear reaction analysis using an F § beam, in combination with multiple-internal-reflection infrared spectroscopy, was used to determine the total H, N--H, and Si--H bond content in the thin films. The details of these techniques have also been reported previously (4,11,12,20).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Nuclear reaction analysis using an F § beam, in combination with multiple-internal-reflection infrared spectroscopy, was used to determine the total H, N--H, and Si--H bond content in the thin films. The details of these techniques have also been reported previously (4,11,12,20).…”
Section: Resultsmentioning
confidence: 95%
“…Auger sensitivity factors for oxynitride and nitride films were determined using calibrated samples with known concentrations. Details of the Auger electron spectroscopy as applied to nitride and oxynitride films have been reported previously by various authors (4,18,19,20). Nuclear reaction analysis using an F § beam, in combination with multiple-internal-reflection infrared spectroscopy, was used to determine the total H, N--H, and Si--H bond content in the thin films.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma enhanced chemical vapor deposition can be used to create dielectric films for encapsulation (14,15). Thin silicon nitride films have been successfully used to encapsulate InP by several researches (16)(17)(18)(19)(20)(21)(22). Recently, Valco et al reported the composition and furnace annealing characteristics of plasma deposited silicon nitride films on ion implanted InP wafers (16).…”
Section: Discussionmentioning
confidence: 99%
“…The deposition chamber was first etched for 5 rain using a CF4 plasma at 100W to remove deposits from previous runs. Valco and Kapoor have reported that fluorine contamination resulting from the CF4 plasma occurs at the insulator-substrate interface (21). To remove the fluorine contamination the CF4 plasma was followed by a N2 plasma etch (21).…”
Section: Methodsmentioning
confidence: 99%
“…1,6 It has become a standard practice to encapsulate the substrates with a suitable dielectric film ͑Si 3 N 4 , SiO 2 , or AlN͒ providing a reduction of the volume which has to be saturated with P in the process of annealing. 10,11 Recently, within the scope of alternative open-tube diffusion method, deposited thin films serving as encapsulants and containing Zn ͑Zn 3 P 2 , nonstoichiometric ZnO, SiO 2 doped by Zn͒ have been employed as a diffusion source of p-dopant ͑Zn͒. [12][13][14][15][16][17][18] During annealing, the thin films protect the InP surface from the thermal decomposition and, moreover, Zn acting as an acceptor diffuses into InP.…”
Section: Introductionmentioning
confidence: 99%